1991
DOI: 10.1093/carcin/12.7.1307
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in expression and methylation of specific gene in livers of rats fed a cancer promoting methyl-deficient diet

Abstract: We have reported earlier that hypomethylated DNA is rapidly induced in the livers of male Fischer rats fed an extremely methyl-deficient diet (MDD). The early effects of dietary methyl deficiency on the expression of several genes in the livers of such animals have now been investigated. Poly(A)+ RNA was isolated from the livers of rats fed MDD or a similar diet supplemented with adequate supplies of choline, methionine, folic acid and vitamin B12 (CSD) for periods ranging from 1 to 4 weeks. The levels of mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 0 publications
1
49
0
4
Order By: Relevance
“…Cellular methyltransferases that have been shown experimentally to be inhibited by SAH include catecholamine-O-methyltransferase (39), phosphatidylethanolamine methyltransferase (46), histone methyltransferase (18), DNA methyltransferase (18,26,47), tRNA and mRNA methyltransferases (48,49), acetylserotonin methyltransferase (50), and histamine N-methyltransferase (51). The functional consequences of decreased cellular methylation are significant and include central nervous system demyelination (52,53), reduced neurotransmittor synthesis (39,50), decreased chemotaxis and macrophage phagocytosis (54,55), altered membrane phospholipid composition and membrane fluidity (56,58), altered gene expression (23,59,60), and cell differentiation (61,62). It is likely that the K i for SAH varies with different cellular methyltransferases and also varies according to tissue priorities and subcellular methyltransferase distribution (63).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular methyltransferases that have been shown experimentally to be inhibited by SAH include catecholamine-O-methyltransferase (39), phosphatidylethanolamine methyltransferase (46), histone methyltransferase (18), DNA methyltransferase (18,26,47), tRNA and mRNA methyltransferases (48,49), acetylserotonin methyltransferase (50), and histamine N-methyltransferase (51). The functional consequences of decreased cellular methylation are significant and include central nervous system demyelination (52,53), reduced neurotransmittor synthesis (39,50), decreased chemotaxis and macrophage phagocytosis (54,55), altered membrane phospholipid composition and membrane fluidity (56,58), altered gene expression (23,59,60), and cell differentiation (61,62). It is likely that the K i for SAH varies with different cellular methyltransferases and also varies according to tissue priorities and subcellular methyltransferase distribution (63).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that a diet deficient in methyl groups provoked the demethylation of c-myc, c-fox, H-ras, and p-53 genes (Bhave et al, 1988;Christman et al, 1993;Dizik et al, 1991;Pogribny et al, 1995;Zapisek et al, 1992). In other studies, supplementation of methyl groups affected the methylation status and gene expression of several genes (Garcea et al, 1989;Kano et al, 2013).…”
Section: Gene Methylation and Foodmentioning
confidence: 98%
“…In contrast, methyl-rich (fortified with choline and methionine) diets prevent or reduce these effects in the liver (147)(148)(149). Changes in the expression levels of protooncogenes and decreased expression of growth factors and growth factor receptors occur in animals on methyl-deficient diets (143,150,151). The increased protooncogene expression correlates with hypomethylation of the protooncogenes (143,150).…”
Section: Target Populationsmentioning
confidence: 99%
“…Changes in the expression levels of protooncogenes and decreased expression of growth factors and growth factor receptors occur in animals on methyl-deficient diets (143,150,151). The increased protooncogene expression correlates with hypomethylation of the protooncogenes (143,150). Collectively, these data suggest that hypomethylation of DNA results in changes in the expression of genes involved in cellular growth control (143,148).…”
Section: Target Populationsmentioning
confidence: 99%